Accelerating the Provision of Safe Water Supply in Urban and Rural Areas of Indonesia - Sutomo, Sumengen; Sagala, Salord; Sutomo, Bebi; Winarti, Sri; Sanjaya, Gelant (UI Scholars Hub, 2021)
Over the past 100 years, the provision of a safe water supply to drink in Indonesia has been slowly progressed with low coverage. The majority of the population does not have access to safe water. Morbidity and mortality of water-related diseases, including diarrhea, are very high. The provision of safe water is not a technological issue but good water management that comprises content, institutional, and communication layer. This paper provided information for strategic and operational decisions to accelerate the provision of safe water services in urban and rural areas. Benchmarking good water management with the characteristics of the water supply location is required to improve the health status of the population, mainly the poor urban and rural areas with limited resources, including time and cost.